Intrathoracic complications associated with trans‐femoral transcatheter aortic valve replacement: Implications for emergency surgical preparedness. Issue 3 (3rd December 2019) - Hodson, Robert W.; Jin, Ruyun; Ring, Michael E.; Gafoor, Sameer; Verburg, Shawnna; Lehr, Eric J.; Spinelli, Kateri J.
Abstract: Background: Intrathoracic complications (ITC) requiring emergency surgical intervention occur during transcatheter aortic valve replacement (TAVR). Objectives: Characterize the incidence, outcomes and predictors of ITC in a large cohort of transfemoral (TF) TAVR cases over a 5 year period. Methods: Retrospective registry and chart review of all nonclinical trial TF‐TAVR patients from seven centers within one hospital system from 2012–2016. ITC were defined as cardiac perforation, new or worsening pericardial effusion/tamponade, annular rupture, thoracic aortic injury, aortic valve dislodgement, and coronary artery occlusion. Procedural and 30‐day outcomes and 1‐year mortality were compared between ITC and no ITC patients. Multivariable logistic regression was used to identify predictors of ITC. Results: Over the study period, 1, 581 patients had TF‐TAVR and 68 ITC occurred in 46 patients (2.9%). The most common ITCs were pericardial effusion/tamponade (59%), cardiac perforation (33%), and valve dislodgement (33%). ITC rate did not decline over time (rate (95% confidence interval) for 2012 = 0% (0–8.8%), 2013 = 1.3% (0–7.2%), 2014 = 4.4% (2.2–8.0%), 2015 = 3.5% (2.0–5.6%), and 2016 = 2.4% (1.5–3.8%)). ITC patients had worse 1‐year survival (ITC: 60.7% (45.1–73.1%), no ITC: 88.7% (87.0–90.3%); p < .001). The majority of ITC patient deaths occurred within the first 30 days. Multivariable models to predict ITC were not successful. Conclusions: ITC did not decline over time in our cohort. Predictors of ITC could not be identified. While these events are rare, they are associated with worse procedural outcomes and mortality. Heart teams should continue to be prepared for emergency intervention.